Small cell carcinoma of the ovary, hypercalcemic type: a mini review - Tripepi, Marta; da Costa, Ana G.; Chi, Dennis S.; Lima, Jorge; Casanova, João (Frontiers in Oncology, 2025)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT) is a rare and highly aggressive ovarian neoplasm, predominantly affecting young women, often in their second or third decade of life. Despite its distinctive clinical and pathological features, diagnosis is frequently delayed due to overlapping characteristics with other small round blue cell tumors. A hallmark of SCCOHT is the biallelic inactivation of the SMARCA4 gene, which leads to loss of BRG1 protein expression and disrupts epigenetic regulation via the SWI/SNF chromatin-remodeling complex. Unlike many other malignancies, SCCOHT exhibits low mutational burden and diploid karyotype, suggesting that epigenetic dysregulation, rather than genomic instability, is the underlying oncogenic mechanism. Clinically, SCCOHT often presents with nonspecific abdominal or pelvic symptoms and is uniquely associated with paraneoplastic hypercalcemia in up to two-thirds of cases. Diagnosis requires a combination of imaging, laboratory evaluation, histopathology, and immunohistochemistry. Treatment is not standardized but typically involves a multimodal approach, including radical surgery and platinum-based chemotherapy, often with multi-agent regimens. The role of radiotherapy is less well defined but may be considered for local control or palliation. Prognosis remains poor, with high recurrence rates and limited response to salvage therapy. Emerging molecular insights have prompted investigations into targeted therapies and immunotherapy, though clinical data are limited. Given the frequent presence of germline SMARCA4 mutations, genetic counseling is strongly recommended, and ongoing research is essential to improve diagnostic accuracy, personalize treatment, and enhance outcomes for this devastating malignancy.